(untitled) (Research, Society and Development, 2022)
Being one of the phytogeographic domains exclusively present in Brazil, the Caatinga occupies approximately 11% of the Brazilian territory and is one of the drylands with the most diversity around the world. The Caatinga is home to a floristic variety that carries a plurality of bioactive compounds capable of reversing physiological disorders. Many bioactive products from Caatinga species have anti-inflammatory and healing potential. The present review aimed to summarize the works that explored the anti-inflammatory and healing activities of plant species present in this phytogeographic domain. The articles were selected from the databases: Elsevier, Springer links, and PubMed to build the present review. In total, 39 plant species were identified, which were studied about their biological potential with experimental assays, and we’ve discussed how its compounds are related to the anti-inflammatory and healing activities. Our results highlight that the most studied product obtained from those plant species is the plant extract, and still those studies aren’t clear about its phytochemical profile. On the other hand, the research focused on plant oils provides a better understanding of how Caatinga plant species promote anti-inflammatory and wound healing action.